2020
DOI: 10.1192/bjp.2020.151
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine treatment and risk of COVID-19 infection: retrospective cohort study

Abstract: Background Clozapine, an antipsychotic with unique efficacy in treatment-resistant psychosis, is associated with increased susceptibility to infection, including pneumonia. Aims To investigate associations between clozapine treatment and increased risk of COVID-19 infection in patients with schizophrenia-spectrum disorders who are receiving antipsychotic medications in a geographically defined population in London, UK. Method Using information from South London and Maud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 24 publications
4
96
1
5
Order By: Relevance
“…Adverse reactions to clozapine include neutropenia (2.7% of patients) which can prefigure an impending life-threatening agranulocytosis, (0.4% of patients) ( Atkin et al, 1996 ; Gee and Taylor , 2020; Pandarakalam, 2020 ). Clozapine treatment is also associated with diabetes, obesity, pulmonary disease ( Gee et al, 2020 ; Dragoi et al, 2020 ) and a reported increased risk of COVID-19 infection ( Govind et al, 2020 ). Switching to an alternative antipsychotic in patients clinically stable on clozapine is challenging, both for clinicians and patients, as this strategy is associated with a high risk of relapse due to the high likelihood of patients who have required treatment with clozapine being resistant to treatment with other antipsychotics ( Butler et al, 2020 ; Chiappini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adverse reactions to clozapine include neutropenia (2.7% of patients) which can prefigure an impending life-threatening agranulocytosis, (0.4% of patients) ( Atkin et al, 1996 ; Gee and Taylor , 2020; Pandarakalam, 2020 ). Clozapine treatment is also associated with diabetes, obesity, pulmonary disease ( Gee et al, 2020 ; Dragoi et al, 2020 ) and a reported increased risk of COVID-19 infection ( Govind et al, 2020 ). Switching to an alternative antipsychotic in patients clinically stable on clozapine is challenging, both for clinicians and patients, as this strategy is associated with a high risk of relapse due to the high likelihood of patients who have required treatment with clozapine being resistant to treatment with other antipsychotics ( Butler et al, 2020 ; Chiappini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatrists and healthcare providers involved in monitoring the absolute neutrophil count (ANC) and dispensing the prescription must be aware of the increased risks in clozapine-treated patients with COVID-19. They must communicate and strengthen the monitoring of side effects, including their duration, as the full impact of the COVID-19 pandemic is still unknown [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the causal role of clozapine and comedication with quetiapine in this case is uncertain. One study suggested an increased risk for SARS-CoV-2 infection [ 11 ] in patients treated with clozapine but does not report the risk for COVID-19 pneumonia. Earlier studies conducted before the SARS-CoV-2 pandemic have suggested an increased risk for pneumonia, probably more concerning bacterial pneumonia [ 21 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite initial concerns, patients with preexisting psychiatric disorders do not seem to be at higher risk of SARS-CoV-2 infection [ 10 ]. One retrospective study suggested that patients treated with clozapine may be at higher risk than patients treated with other antipsychotics, but these results need replication [ 11 ]. Overall, given the extremely widespread population, there are numerous patients with ongoing psychiatric treatment who develop COVID-19 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%